Mapping Global Research on Cognitive Style: A Bibliometric Analysis - Usman, Usman; Akib, Irwan; Sukmawati, Sukmawati (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
Cognitive style refers to individual differences in how people perceive, process, and use information in learning and problem-solving. Understanding these differences is essential for designing effective and equitable instruction. However, no comprehensive bibliometric analysis has yet examined global research trends on cognitive style differences in educational contexts. This study aims to map the intellectual structure and development of research on cognitive styles from 2015 to 2024, identifying the most influential journals, authors, institutions, and countries, as well as emerging thematic trends. Data comprising 277 documents were retrieved from the Scopus database and analyzed using VOSviewer for co-authorship, co-citation, and keyword co-occurrence networks. The findings reveal a steady annual growth in publications, dominated by themes related to learning styles, metacognition, and adaptive learning. The United States and China emerged as the most productive countries, with Learning and Individual Differences as the leading journal. These results highlight the growing scholarly attention to cognitive styles and their implications for personalized learning and instructional innovation. The study contributes a comprehensive overview of the field, serving as a reference for future research, teacher professional development, and curriculum design aimed at improving learning equity and quality.